การพัฒนาไมโครแคปซูลเก็บกักสารให้กลิ่นรสจากใบมะกรูดโดยวิธีโคอะเซอร์เวชันเชิงซ้อน - ศรัญญา เรืองสว่าง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Kaffir lime (Citrus hystrix DC.) leaves are one of the major ingredients in Thai food due to their good flavor and strong fragrance. The objectives of this study were to 1) optimize supercritical carbondioxide extraction of kaffir lime leaves 2) compare kaffir lime leaves extract among supercritical carbondioxide, steam distillation and solvent (hexane) extraction 3) develop microcapsules of kaffir lime leaves extract by complex coacervation technique and 4) evaluate shelflife